2020
DOI: 10.1017/s0144686x20000148
|View full text |Cite
|
Sign up to set email alerts
|

Retirement timing in Italy: rising age and the advantages of a stable working career

Abstract: This article looks at how retirement timing is changing in Italy. A first aim is descriptive and it is to identify recent trends in retirement age, following the pension reform. Then the focus is on factors which may favour or hinder the extension of the working career of older workers. They are studied by looking at the reasons for retirement, introducing the distinction between voluntary and involuntary retirement, and some predictors of retirement. Some of them relate to the work history of individuals, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…The role of grandchildren, as explored by Van Bavel and De Winter [81], is also confirmed: grandchildren are likely to give workers a motivation to retire. With regard to education, our findings differ from the existing literature, which underlines its importance [66,77,82]; conversely, we found no significant influence of the variable when carrying out simulations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The role of grandchildren, as explored by Van Bavel and De Winter [81], is also confirmed: grandchildren are likely to give workers a motivation to retire. With regard to education, our findings differ from the existing literature, which underlines its importance [66,77,82]; conversely, we found no significant influence of the variable when carrying out simulations.…”
Section: Discussioncontrasting
confidence: 99%
“…Bockermann and Ilmakunnas [76] used probit models to study the impact of working conditions on early retirement. Trentini [77] used logit regressions to analyze SHARE data, and concluded that low levels of education and a stable career drive retirement patterns in Italy; in addition, he identified health as a potential factor driving involuntary retirement. SHARE data and event history analysis were used by Macken et al to conclude that education plays a role in explaining involuntary labor market exit across Europe [78].…”
Section: Retirementmentioning
confidence: 99%
“…Disadvantages or advantages can accumulate over time (Bennett & Möhring, 2014;O'Rand, 1996). TRENTINI Unemployment may affect the type of retirement (voluntary or involuntary) and retirement timing (early, on time, later) (Dingemans et al, 2017;Fisher et al, 2016;Hofäcker et al, 2015;Stiemke & Hess, 2022;Trentini, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Late‐career discontinuity resulting from unemployment has received limited attention in recent studies on retirement timing determinants (Blossfeld et al., 2011; Trentini, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, changes in retirement behaviour (driven e.g. by legislative changes) may not be evenly distributed across socio-economic, demographic, educational and occupational groups (Coile et al 2018 ; Radl 2013 ; Trentini 2020 ). For example, increases in retirement ages have mainly taken place among the highly educated (OECD 2017a ; Rutledge 2018 ) and among people with high occupational status (Leinonen et al 2020 ; Qvist 2020 ), and have in general been more pronounced for women than for men (OECD.Stat 2021 ).…”
Section: Introductionmentioning
confidence: 99%